Fenomena Childfree Terhadap Bonus Demografi Islam Di Indonesia - Ayu Wulandari; Finfi Azahro; Hilman Fadhilah; Mhd. Aksaril Huda Ritonga; Siti Hamidah (Lembaga Pengembangan Kinerja Dosen, 2023)
In the last few decades, Indonesia's birth rate has been declining, raising concerns about an unattainable demographic dividend. This decline in birth rates is partly due to the decision of several muslim couples who choose not to have children or what is known as childfree. The purpose of this research is to discuss the child-free phenomenon among muslim communities in Indonesia and its implications for the sustainability of muslims in Indonesia. The method used in this research is a qualitative method that emphasizes literature study. The results of this study present an overview of society's view of the childfree phenomenon based on stigma and social pressure which generally assumes that the choice not to have children cannot be normalized. The conclusions obtained from this research are that the childfree phenomenon is still common in Indonesia, these differences in views are generally influenced by religious and demographic factors which have concerns about the reduced number of generations of Muslims in Indonesia. Recommendations that need to be considered are conducting further research, because the childfree phenomenon is still relatively new in Indonesia, and further research is still needed to understand the perspective of society as a whole.